The harmful intestinal microbial community accumulates during DKD exacerbation and microbiome–metabolome combined validation in a mouse model - Shang, Jin; Cui, Wen; Guo, Ruixue; Zhang, Yiding; Wang, Peipei; Yu, Wei; Zheng, Xuejun; Wang, Ting; Dong, Yijun; Zhao, Jing; Ding, Suying; Xiao, Jing; et al. (Frontiers in Endocrinology, 2022)
Objective Diabetic kidney disease (DKD) is one of the most prevalent complications of diabetes mellitus (DM) and associated with gut dysbiosis. We aim to build diagnostic model to aid clinical practice and uncover crucial harmful microbial community that contributes to DKD pathogenesis and exacerbation. Design We recruited 180 DKD patients and 348 non-DKD populations (138 DM and 210 healthy volunteers) and compared the microbial alterations. Then the 180 DKD patients were stratified into 4 groups based on clinical stages and underwent gut microbiota analysis. We established DKD rat models and healthy fecal microbiota transplantation (FMT) model to validate the effects of gut microbiota in DKD and select the potential harmful microbial community. Untargeted metabolome-microbiome combining analysis of rat models help decipher the pathogenetic mechanism from metabolic perspective. Results: The diversity of gut microbiome was significantly decreased in DKD patients when compared with non-DKD populations and was increased in the patients with more advanced DKD stage. The severity of DKD rats was relieved after healthy gut microbiota reconstruction. The common harmful microbial community were accumulated in the subjects with more severe DKD phenotypes (i.e., DKD and DKD5 patients and DKD rats). The harmful microbial community were positively associated with the serum injurious metabolites (e.g., cholic acid, hippuric acid). Conclusion: Fecal microbial community altered markedly in DKD. Combining the fecal analysis of both human and animal model selected the targeted accumulated harmful pathogens. Partially recovering healthy gut microbiota can relive DKD phenotypes via influencing pathogens’ effect on DKD rats’ metabolism.